Effect of hypercholesterolemia alone or combined with hypertension on the degree of coronary artery stenosis in patients with coronary heart disease angina pectoris: A medical records based retrospective study protocol. Issue 38 (18th September 2020) - Xue, Xiaoxue; Liu, Yijia; Yang, Mingjie; Wang, Shuo; Huang, Mengnan; Gao, Shuming; Xu, Yilan; Gao, Shan; Li, Lin; Yu, Chunquan
Abstract: Background: Coronary heart disease (CHD) is the leading cause of death globally. Angina pectoris is closely associated with coronary artery insufficiency, which seriously affects the quality of life and work of patients. Hypercholesterolemia and hypertension (HTN) are risk factors for CHD angina pectoris. The correlation between hypercholesterolemia with or without HTN and the severity of coronary arteries has not been clarified. Objective: To explore the correlation between hypercholesterolemia and the degree of coronary artery stenosis (CAS) of CHD angina pectoris, and to further research the influence of HTN on total cholesterol level and CAS, so as to provide guidance for clinical prevention and treatment. Methods: A multicenter, retrospective clinical study was conducted in the medical records management system of 6 hospitals in Tianjin. Patients who were suffered from CHD angina pectoris and aged from 35 to 75 years old are involved. They hospitalized in the Department of Cardiology between September 1, 2014, and September 1, 2019, and underwent coronary angiography. We divide patients into 3 groups based on the total cholesterol level, the degree of CAS is evaluated by Gensini score, and further divide them into 6 subgroups based on with or without HTN. Collect and analyze the demographics, laboratory information, clinical outcome data, and coronary angiographic data of patients. Conclusion: Through clinical research data, the study will help to provide guidance for the prevention and treatment of CHD angina pectoris complicated with diseases and promote further research.